Phenolic Metabolism Explains Bitterness and Pungency of Extra Virgin Olive Oils - Sonia Tomé-Rodríguez; Francisco Barba-Palomeque; Mónica Calderón-Santiago; José María Penco-Valenzuela; Feliciano Priego-Capote (Foods)
Organoleptic features allow extra virgin olive oil (EVOO) to be distinguished from other commercial categories and to determine consumer preferences. In this study, we evaluated the influence of the phenolic content on the intensity of two characteristic attributes, namely, bitterness and pungency. The organoleptic analysis was carried out by a panel of trained tasters, who categorized a set of 200 EVOO samples produced in two consecutive crop seasons into three intensity levels (“Delicate”, “Medium”, and “Robust”) according to current regulations. The total phenolic content was correlated with the intensity of both attributes, but a different contribution was identified for individual phenols. For bitterness, aglycone isomers of oleuropein and ligstroside provided over 70% discrimination power (estimated by receiver operating characteristic analysis), while oleocanthal and oleacein were associated with a decrease in bitterness intensity. In addition, the intensity of pungency intensity was related to the content of oleocanthal, oleomissional, and oleokoronal, as they allowed the classification of about 75% of the “Robust” pungency EVOOs. With these premises, it is possible to obtain olive oils with the desired intensity of bitterness and pungency by controlling the factors that influence phenolic metabolism.